Priority directions of industrial and innovative development of Kazakhstan: current state and prospects - Alina, G.B.; Daribayeva , A.K. (BUKETOV BUSINESS REVIEW, 2018)
The article considers the importance of industrial and innovative development of the Republic of Kazakhstan as a key direction of the country’s economic growth and the main directions of state policy in the sphere of scientific, technical and innovative activity. The authors analyzed the main results of the implementation of the State Program for Forced Industrial Innovative Development for 2010–2014, and also the expected annual social and economic effects within the framework of the current State Program for Industrial and Innovative Development for 2015–2019. The structure of sources of financing of technological innovations is studied and analyzed. Particular attention is paid to the study of foreign experience of financial investments in the science of economically developed countries. The analysis on the regions of Kazakhstan in the part «Gross added value» was carried out. Based on the analysis and study of foreign experience, the authors identified the main problems that impede active industrial-innovative development, and suggested a number of recommendations on Kazakhstan’s exit from the economic crisis. The conducted researches allowed the authors to develop, in particular, the following measures: increase of financing for modernization and technical reequipment of existing and new enterprises in priority strategic sectors such as agribusiness, construction industry, oil refining, metallurgy, chemical industry, energy, transport and telecommunications infrastructure, engineering and tourism